System motywowania jako narzędzie wspierania przedsiębiorczości - Kmiotek, Krystyna; Lewicka, Dagmara; Oleśniewicz, Piotr (A System of Motivating as a Tool for Enterprise Promoting, 2006)
Authors, on basis of carried out research, have tried to answer the question whether systems of motivating, existing in companies create suitable conditions for internal enterprise development and stimulate employees to behave enterprisingly. This article contains discussion of connection between enterprise and some selected elements of the motivating system such as a company information policy, opportunities to increase qualifications and a chance to reveal creativity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 291-298